Post global pandemic and national paradigm of resilience of Indonesian SMEs - Fatimah, Nuzulul; Wibisono, Muhammad Gunawan; Fareed, Abid (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
Indonesia has a big potential of development by boosting up the SMEs. The SMEs seems neglected by its history on Indonesia as the main focus remained on public sector. The SMEs particular in large scale manufacturing units beyond the government, bank, and liberalization. As the SMEs sector period withdraw their development because of lack skill and function. In this research, SMEs sector in Indonesia as an object using the bibliography methodological to analyze the paradigm and liberate realizing the need to specify the key terms for purposes resilience on post global pandemic. Through innovative business opportunities and creating value by individuals, it is an effort to create value. In addition, this value creation can be done by providing encouragement to manage the risks of a project, improving communicative and management skills in helping the movement of people, fast materials and financial resources for project success.